2012
DOI: 10.1039/c2pp25144b
|View full text |Cite
|
Sign up to set email alerts
|

Photopheresis (extracorporeal photochemotherapy)

Abstract: Photopheresis is a form of phototherapy where specialized equipment is used to isolate a leukocyte fraction from the peripheral blood which is then exposed to photoactivated 8-methoxypsoralen and reinfused into the patient. At the time of its invention the treatment was conceptually based on the hypothesis of T cell vaccination, i.e. the observation in experimental studies that exposure of the immune system to physically modified T cell clones leads to a specific inhibition of T cell mediated autoimmunity. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 59 publications
1
22
0
1
Order By: Relevance
“…18 Nausea was a common side effect to the oral formulation of 8-MOP but has now been eliminated with the introduction of the liquid formulation directly injected into the collection bag. 15 A single case of grade III anemia was reported in a patient with SS undergoing treatment with bexarotene and ECP caused by undiagnosed cold agglutinin disease, which was suspected when agglutinated blood was noted in the centrifuge bowl of the photopheresis device. 73 …”
Section: Adverse Effectsmentioning
confidence: 98%
See 2 more Smart Citations
“…18 Nausea was a common side effect to the oral formulation of 8-MOP but has now been eliminated with the introduction of the liquid formulation directly injected into the collection bag. 15 A single case of grade III anemia was reported in a patient with SS undergoing treatment with bexarotene and ECP caused by undiagnosed cold agglutinin disease, which was suspected when agglutinated blood was noted in the centrifuge bowl of the photopheresis device. 73 …”
Section: Adverse Effectsmentioning
confidence: 98%
“…12 The question arose whether the malignant circulating lymphocytes in SS would respond to PUVA phototherapy if the energy could be directed at blood cells. Initial experiments performed in Edelson's laboratory found evidence that an anti-idiotypic response to diseasespecific T-cell receptors could be found after exposing autoreactive T cells from rats to 8-MOP and UV-A in an ex vivo system inspired by Cohen and colleagues [13][14][15] at the Weizmann Institute. With the help of engineers at Therakos, Inc, a subsidiary of Johnson and Johnson, Edelson 16 designed a device that could expose a fraction of leukocyte-enriched blood, removed from patients after they had taken psoralen, to UV-A light in an extracorporeal system before returning the treated blood products back to the patients.…”
Section: Historical Aspectsmentioning
confidence: 98%
See 1 more Smart Citation
“…E xtracorporeal photopheresis (ECP) is an immunomodulatory cellular therapy exhibiting clinical efficacy for attenuation of graft-versus-host disease (1-3) and solid organ transplant rejection (4) and for the treatment of cutaneous (5-7) and noncutaneous T cell lymphomas (8). ECP involves collection of leukocytes by apheresis that are exposed to 8-methoxypsoralen (8-MOP) and UVA light and retransfused into the patient (9). Numerous studies have reported that ECP can expand the number of regulatory T cells (Tregs), providing a rationale to understand the immunoregulatory efficacy of ECP for the treatment of graft-versus-host disease and solid organ transplant rejection (10)(11)(12).…”
mentioning
confidence: 99%
“…Upregulation of HSPs can be induced by a number of stresses including temperatures, alcohol, heavy metals, oxidants, UV, and tobacco smoke and is usually followed by temporarily increased resistance to the particular stress involved [158]. French et al [159] provide a highly plausible link between mobile phone radiation and HSP induced cancer.…”
Section: Heat Shock Protein(s) (Hsp)mentioning
confidence: 99%